Media and information literacy : made simple - Bernales, Rolando A.; Geronimo, Ramir B.; Orpia, Justin Kylo-Marc M.; Aldaca, Vanesa Amor T. (Malabon City : Mutya Publishing House, Inc., 2019)
"MIL is a course that introduces the learners to basic understanding of media and information as channels of communication and tools for the development of individuals and societies. This textbook also aims to develop students to be creative and critical thinkers as well as responsible users and competent producers of media and information".
Includes bibliographical references.
Keywords: Communication; Mass media